ADP-receptor blockade: A case for personalised pharmacotherapy? - Zürn, Christine S.; Geisler, Tobias; Gawaz, Meinrad (Thrombosis and Haemostasis, 2010)
The dual antiplatelet therapy consisting of aspirin and the ADP-receptor blocker clopidogrel is the current standard medication after acute coronary events. However, clopidogrel is characterised by a high interindividual response variability, insufficient inhibition of platelet aggregation in a significant number of patients, relatively slow onset of efficacy and potential interaction with different co-medication via diverse hepatic cytochrome enzymes. In various trials, response variability of clopidogrel was translated into a higher rate of recurrent cardiovascular events. Different clinical and non-genetic factors contribute to the phenomenon of clopidogrel response variability. An individualised antithrombotic pharmacotherapy taking these factors into account, including the definition of status of response, verification of the efficacy by standardised platelet function testing, intensified or alternative platelet inhibition would be the ultimate goal for patients treated with clopidogrel. Currently, new drugs are on the way and promise a more consistent efficacy and smaller amount of response variability. However, the bleeding risk in subgroups of patients and further side effect profile remains to be clearly defined. Therefore, risk stratification models are warranted to identify patients who benefit from personalised pharmacotherapy in terms of improved clinical net benefit. In this review, we discuss treatment failure of clopidogrel based on platelet function testing, the mechanism of established and new ADP-blockers as well as new therapeutic principles.
Keywords: ADP-receptor blockers; thienopyridines; clopidogrel; response variability; prasugrel; platelet function testing